1997
DOI: 10.1021/om960790e
|View full text |Cite
|
Sign up to set email alerts
|

Insertions of Allenes into Palladium−Carbon Bonds of Complexes Containing Bidentate Nitrogen Ligands. Structural and Mechanistic Studies

Abstract: The insertion reactions of the allenes propadiene and 1,2-heptadiene in the Pd-C bond of complexes (NkN)Pd(R)X Cl, Br) have been investigated. An X-ray crystal structure determination of (8-PQ)Pd{(1-3-η)-2-methylpropenyl}Cl exhibited the unexpected monodentate coordination of the nitrogen ligand. The monodentate coordination in apolar solvents and bidentate coordination in polar solvents was demonstrated by means of NOE NMR experiments. Kinetic measurements revealed that the reactions are first order in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 78 publications
1
33
0
Order By: Relevance
“…provided strong evidence that insertion reactions in neutral complexes containing bidentate nitrogen ligands occur via Results and Discussion intermediates in which these ligands are coordinated in a unidentate fashion. [12] [13] [14] [15] …”
Section: Novel Methyl Complexes [Pd(me)(n-n-n)]x (N-n-n =mentioning
confidence: 99%
“…provided strong evidence that insertion reactions in neutral complexes containing bidentate nitrogen ligands occur via Results and Discussion intermediates in which these ligands are coordinated in a unidentate fashion. [12] [13] [14] [15] …”
Section: Novel Methyl Complexes [Pd(me)(n-n-n)]x (N-n-n =mentioning
confidence: 99%
“…In some examples it has been reported that a ligand of higher basicity makes the apparent rotation more difficult, [21] while increased steric hindrance of the N-donor ligand can facilitate [20,29] or slow down [21] the process. Negative entropies of activation have been found in some cases [29,32] and it has been reported that the process takes place more easily with coordinating anions [19,29,31] or solvents such as DMSO. [20b] It has also been reported that the addition of ligand or water has a negligible effect on the process in a number of examples; [18,21] other examples have been described where the effect of adding ligand or chlorides is accelerative.…”
Section: Introductionmentioning
confidence: 99%
“…The latter possibility might well occur as structural studies on Pd-η 3 -allyl complexes and (2,9-dimethyl-1,10-phenanthroline)Pt(X) 2 L complexes (L ) C 2 H 4 , CO, PPh 3 , ONPh) revealed monodentate coordination of a nitrogen ligand for flexible ligands as well as for rigid ones. [31][32][33] To obtain more insight into the mechanism of CO insertion, we turned our attention to insertion of the isoelectronic isocyanides. Isocyanides might allow the observation of intermediate complexes and variation of electronic and steric factors by variation of the R group on the nitrogen atom, and moreover, it would be of great interest to look at the possibility for the direct synthesis of the polyimine analogue of polyketone.…”
Section: Introductionmentioning
confidence: 99%